Earnings Quality in Motion: Analyzing the Role of Profitability, Firm Characteristics, and Audit Practices (2019–2023) - Wijaya, Evelyn; Simanjuntak, Edita Yolanda Malika; Suhermin, Suhermin (Research in Accounting Journal (RAJ), 2024)
The transportation and logistics sector plays a crucial role in supporting consumption activities across communities and industries, including trade, services, manufacturing, and construction. These sectors are widely recognized as key drivers of national economic growth. This study aims to examine the impact of Profitability, Company Size, Company Age, Audit Quality, and Audit Committee on Earnings Quality within the transportation and logistics sector during the period 2019–2023. The research utilizes secondary data derived from company financial statements, with a purposive sampling method employed to select the sample. A total of 22 companies were included in the study. Quantitative analysis was conducted using SmartPLS. The findings reveal that Company Size has a negative effect on Earnings Quality, while Company Age has a positive effect. Meanwhile, Profitability, Audit Quality, and Audit Committee were found to have no significant effect on Earnings Quality. High-quality earnings reflect a company’s true financial performance and serve as a reliable indicator for predicting future earnings.